Cationic nanoparticle as an inhibitor of cell-free DNA-induced inflammation. Issue 1 (December 2018) - Liang, Huiyi; Peng, Bo; Dong, Cong; Liu, Lixin; Mao, Jiaji; Wei, Song; Wang, Xinlu; Xu, Hanshi; Shen, Jun; Mao, Hai-Quan; Gao, Xiaohu; Leong, Kam; et al.
Abstract Cell-free DNA (cfDNA) released from damaged or dead cells can activate DNA sensors that exacerbate the pathogenesis of rheumatoid arthritis (RA). Here we show that 40 nm cationic nanoparticles (cNP) can scavenge cfDNA derived from RA patients and inhibit the activation of primary synovial fluid monocytes and fibroblast-like synoviocytes. Using clinical scoring, micro-CT images, MRI, and histology, we show that intravenous injection of cNP into a CpG-induced mouse model or collagen-induced arthritis rat model can relieve RA symptoms including ankle and tissue swelling, and bone and cartilage damage. This culminates in the manifestation of partial mobility recovery of the treated rats in a rotational cage test. Mechanistic studies on intracellular trafficking and biodistribution of cNP, as well as measurement of cytokine expression in the joints and cfDNA levels in systemic circulation and inflamed joints also correlate with therapeutic outcomes. This work suggests a new direction of nanomedicine in treating inflammatory diseases. Cell-free DNA (cfDNA) released from damaged or dead cells can activate DNA sensors that exacerbate the pathogenesis of rheumatoid arthritis (RA). Here the authors use 40 nm cationic nanoparticles to scavenge cfDNA, and demonstrate the potential for nanomedicine to relieve debilitating RA symptoms.